Biosynthesis of Ag/Cu bimetallic nanoparticles using Ricinus communis and their antibacterial and antifungical activity. (28th May 2020) - López-Ubaldo, Fernando; Sánchez-Mendieta, Víctor; Olea-Mejía, Oscar F; González-Pedroza María, Sol; Morales Luckie, Raúl A
Abstract: This work demonstrates an efficient, low-cost and environmentally friendly synthetic method of Ag/Cu bimetallic nanoparticles (NPs), which allows taking advantage of renewable resources, using Ricinus Communis leaf extract as bioreducing and passivating agent. By varying the metal salt precursors of AgNO3 and CuSO4 .5H2 O concentrations, the stable bimetallic NPs were obtained. The Ag/Cu bimetallic NPs were characterised using ultraviolet-visible absorption spectroscopy (UV–vis), Fourier-transform infrared spectroscopy (FTIR), X-ray dispersive energy spectroscopy (EDS), and scanning and transmission electron microscopy (SEM and TEM). In all cases, the particles size is less than 100 nm. The 10:90 Ag/Cu system has the best control of morphology (spheroid) and size in range of 10–25 nm ( X ̄ = 18 nm, σ  = 9). Selected area electron diffraction patterns (SAED) are in concordance with JCPDF cards for silver and copper face-centered cubic (fcc) crystal structures. Microbiological susceptibility was tested by disc diffusion, minimum inhibitory concentration (MIC) and minimal lethal concentration (MLC) methods, with the following microorganism strains: Staphylococcus aureus (gram +), Escherichia coli (gram −) and Aspergillus niger (fungus). The MIC concentration for the three strains was found to range from 1.25 to 2.45 μ g and the MLC allowance ranges from 2.45 to 9.81 μ g.